Aortocaval Fistula in Rat: A Unique Model of Volume-Overload Congestive Heart Failure and Cardiac Hypertrophy. (11th January 2011) - Abassi, Zaid; Goltsman, Ilia; Karram, Tony; Winaver, Joseph; Hoffman, Aaron
Abstract : Despite continuous progress in our understanding of the pathogenesis of congestive heart failure (CHF) and its management, mortality remains high. Therefore, development of reliable experimental models of CHF and cardiac hypertrophy is essential to better understand disease progression and allow new therapy developement. The aortocaval fistula (ACF) model, first described in dogs almost a century ago, has been adopted in rodents by several groups including ours. Although considered to be a model of high-output heart failure, its long-term renal and cardiac manifestations are similar to those seen in patients with low-output CHF. These include Na + -retention, cardiac hypertrophy and increased activity of both vasoconstrictor/antinatriureticneurohormonal systems and compensatory vasodilating/natriuretic systems. Previous data from our group and others suggest that progression of cardiorenal pathophysiology in this model is largely determined by balance between opposing hormonal forces, as reflected in states of CHF decompensation that are characterized by overactivation of vasoconstrictive/Na + -retaining systems. Thus, ACF serves as a simple, cheap, and reproducible platform to investigate the pathogenesis of CHF and to examine efficacy of new therapeutic approaches. Hereby, we will focus on the neurohormonal, renal, and cardiac manifestations of the ACF model in rats, with special emphasis on our own experience.